Vacancy-engineered bismuth-based semiconductor with enhanced photocatalytic activity: A review. (January 2022) - Liu, Sitong; Sun, Jianpeng; Ren, Guangmin; Meng, Xiangchao
Abstract: The introduction of vacancies has been increasingly attracted attentions to improve photocatalytic activity of semiconductors including bismuth-based photocatalysts. Theoretically, vacancies cannot only narrow the band gap to enable the semiconductor to capture more visible light in the solar light spectrum, but also provide more reactive sites on the surface of photocatalysts. In this review, recent progress on vacancy-engineered bismuth-based semiconductors in photocatalysis has been comprehensively summarized and discussed, including the fabrication methods, characterization approaches to detect the vacancies, and functions of vacancy in improving the photocatalytic activity in various applications. Finally, we proposed the challenges and suggested strategies for future work on vacancy-engineered bismuth-based semiconductor in photocatalysis. Graphical abstract: Image 1 Highlights: Vacancy engineered bismuth-based photocatalysis is comprehensively reviewed. Functions of vacancies for various BBS-based photocatalytic applications have been introduced. Suggestions for future works in this research area have been suggested.